2011
DOI: 10.1063/1.3571473
|View full text |Cite
|
Sign up to set email alerts
|

Communication: Identification of the molecule–metal bonding geometries of molecular nanowires

Abstract: Conductive probe AFM study of Pt-thiol and Au-thiol contacts in metal-molecule-metal systems

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
42
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 31 publications
6
42
0
Order By: Relevance
“…These IETS experiments together with the theoretical work demonstrated conclusively that particular molecular species are involved in electrical conduction through metal-molecule-metal junctions. It has also been shown that IETS can be sensitive to the molecular conformation [29,38,74,78], the orientation of molecules relative to the electrodes [56,77] and the gold-sulfur atomic bonding geometries at the molecule-metal interfaces [75,76,78].…”
Section: Introductionmentioning
confidence: 99%
“…These IETS experiments together with the theoretical work demonstrated conclusively that particular molecular species are involved in electrical conduction through metal-molecule-metal junctions. It has also been shown that IETS can be sensitive to the molecular conformation [29,38,74,78], the orientation of molecules relative to the electrodes [56,77] and the gold-sulfur atomic bonding geometries at the molecule-metal interfaces [75,76,78].…”
Section: Introductionmentioning
confidence: 99%
“…Electronic mail: asaffarz@sfu.ca of fullerene dimers, C 120 in which the two C 60 molecules are connected by a cyclic C 4 unit, is the simplest one and has the lowest energy as well as interesting physical and chemical properties [22], we have chosen this isomer of the C 60 dimer in our calculation. We note that, the electronic transport properties of a pure C 60 dimer [23], N and B doped C 60 dimer [24], and Li@C 60 dimer [25] have been reported theoretically, however, encapsulation of magnetic atoms in fullerene dimers has not been addressed in the previous theories.We consider an endohedral fullerene Co@C 60 dimer contacted via single gold atoms (as in some experimentally realized single-molecule electronic devices [26,27]) by semi-infinite non-magnetic electrodes, as shown in Fig. 1.…”
mentioning
confidence: 99%
“…We consider an endohedral fullerene Co@C 60 dimer contacted via single gold atoms (as in some experimentally realized single-molecule electronic devices [26,27]) by semi-infinite non-magnetic electrodes, as shown in Fig. 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the spin-valve effect that we predict here does not depend critically on the gold nano-cluster size. The non-magnetic leads are modeled as a small number of semi-infinite one-dimensional ideal channels that represent macroscopic electron reservoirs (as in previous studies of electron and spin transport through single molecules with gold contacts 9,10,[21][22][23] ) to simulate moderately weak coupling between the nano-device and electrodes.The geometries of our nano-devices are shown in Fig. 1(a) and (b).…”
mentioning
confidence: 99%